2018
DOI: 10.1002/tox.22637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dihydromyricetin on ARPE‐19 cell migration through regulating matrix metalloproteinase‐2 expression

Abstract: Dihydromyricetin (DHM), a flavanonol compound in Ampelopsis grossedentata, possesses several biological activities. However, the molecular mechanism underlying the effects of DHM on human proliferative vitreoretinopathy (PVR) remains unclear. We explored the effects of DHM on cell migration and the metastasis‐promoting proteins in human retinal pigment epithelial (RPE) cells (ARPE‐19 cells). Our results revealed that DHM attenuated ARPE‐19 cell invasion and migration by reducing matrix metalloproteinase‐2 (MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Cancer cells secrete numerous proteases, including MMPs, urokinase plasminogen, and cathepsin, to degrade the basement membrane and extracellular matrix, thus facilitating the passage of cancer cells into the circulation to metastasize to distant organs [26]. Furthermore, MMP-2 is associated with metastasis in oral cancer, nasopharyngeal carcinoma, eye cancer, and brain cancer [23,[27][28][29]. Therefore, we expected that MMP-2 inhibition would suppress metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells secrete numerous proteases, including MMPs, urokinase plasminogen, and cathepsin, to degrade the basement membrane and extracellular matrix, thus facilitating the passage of cancer cells into the circulation to metastasize to distant organs [26]. Furthermore, MMP-2 is associated with metastasis in oral cancer, nasopharyngeal carcinoma, eye cancer, and brain cancer [23,[27][28][29]. Therefore, we expected that MMP-2 inhibition would suppress metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…ARPE‐19 cells were adjusted to 1 × 10 5 cells/well in the presence of kaempferol (0, 25, 50, 75, and 100 μM) for 24 hours. The cell migration and invasion assay was performed as described by Lin et al The invaded cells were photographed using a light microscope and the data are expressed as the average cell number in 4 fields as previously described …”
Section: Methodsmentioning
confidence: 99%
“…DHM inhibits the invasion and migration of human retinal pigment epithelial cells (ARPE-19) by decreasing the expression of MMP-2( 64 ). By contrast, Zhang et al ( 65 ) reported that DHM significantly inhibited the migration and invasion of SK-Hep-1 and MHCC97L hepatocellular carcinoma cells by decreasing MMP-9 protein expression, while downregulation of MMP-9 protein expression was closely associated with increased PKC-δ protein levels and decreased phosphorylation of p38, ERK1/2 and JNK in SK-Hep-1 and MHCC97L cells.…”
Section: Multiple Molecular and Cellular Mechanisms Of The Antitumour...mentioning
confidence: 99%